Warrior girls : protecting our daughters against the injury epidemic in women's sports - Sokolove, Michael Y. (New York : Simon & Schuster, 2008)
An examination of the relationship between gender and athletics traces a rise in devastating injuries suffered by young women athletes in recent decades, citing a lack of coach awareness and dangerous disallowances for gender differences.
Amy -- Warrior girls -- Inconvenient truths -- "We can bring it" -- Proving grounds -- Amy : eighteen minutes -- In the OR -- A medical detective story -- Among the plebes -- The ACL witch -- One-trick ponies -- "Are you asking me why I'm doing something I know is bad for kids?" -- "I'm a stressed person" -- Head to toe -- Amy : "I miss it so much" -- Afterword : Prescriptives.
Includes bibliographical references (pages 283-289) and index.
Keywords: Sports for girls; Sports for women; Sports injuries -- Prevention; Sports -- Safety measures